Tracking single cells in live animals using a photoconvertible near-infrared cell membrane label. - Alicia L Carlson; Joji Fujisaki; Juwell Wu; Judith M Runnels; Raphaël Turcotte; Joel A Spencer; Cristina Lo Celso; David T Scadden; Terry B Strom; Charles P Lin (PLoS ONE)
We describe a novel photoconversion technique to track individual cells in vivo using a commercial lipophilic membrane dye, DiR. We show that DiR exhibits a permanent fluorescence emission shift (photoconversion) after light exposure and does not reacquire the original color over time. Ratiometric imaging can be used to distinguish photoconverted from non-converted cells with high sensitivity. Combining the use of this photoconvertible dye with intravital microscopy, we tracked the division of individual hematopoietic stem/progenitor cells within the calvarium bone marrow of live mice. We also studied the peripheral differentiation of individual T cells by tracking the gain or loss of FoxP3-GFP expression, a marker of the immune suppressive function of CD4(+) T cells. With the near-infrared photoconvertible membrane dye, the entire visible spectral range is available for simultaneous use with other fluorescent proteins to monitor gene expression or to trace cell lineage commitment in vivo with high spatial and temporal resolution.